Relation of Mycobacterium tuberculosis mutations at katG315 and inhA-15 with drug resistance profile, genetic background, and clustering in Argentina - Monteserin, Johana (2017)
Fil: Monteserin, Johana. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina.